Investigation of smart economic zone planning scheme - Lei-lei ZHOU; Wei JIANG; Meng WANG; Shi-yan DU (物联网学报, 2017)
The smart economic zone can be viewed as intelligent park platforms built by cloud computing,IoT and other advanced information technology,which is developing rapidly in various industries with the rapid development of domestic economy.Several key technologies,such as Internet of Things,cloud computing,SOA and security information are analyzed in terms of technical architecture firstly.And then focus on the smart economic zone overall construction planning scheme,technical structure selection and evolution route in order to provide a reference model for the industrial park’s wisdom.